Cryopreservation for long-term conservation of cassava genetic resources - Escobar Pérez, Roosevelt H.; Mafla, G.; Roca, W. (International Center for Tropical Agriculture, 1995)
Cassava is mostly growing by resource-limited farmers in the Americas, Africa, Asia and Oceania. The crop is an important source of food and income for millions in the tropics. Vegetative propagation, bulkiness of planting material and risk of genetic erosion make cassava an ideal target for innovative approaches in genetic conservation. At CIAT, an in vitro active gene bank (IVAG) has been established, maintaining under slow growth nearly 5500 clones of the world cultivated and wild Manihot collections. While the IVAG requires periodic subculturing and is labor intensive, ultra-rapid freezing in liquid nitrogen (LN) is ideal as it stops all cell functions, avoiding cell deterioration, to achieve long-term preservation of genotypes. We have developed a basic protocol to recover viable cassava shoot tips from LN with the cultivar (cv.) M Col 22 used as a model, and thereafter reproduced with several cultivars representing wide geographic distribution. Several factors contributed to successful cassava cryopreservation with tissue dehydration being critical; preculture of shoot tips to initiate growth, followed by cryoprotection with sorbitol and DMSO, were also important for obtaining high survival. Rate of plantlet recovery after freezing increased when shoot tips were incubated in a low concentration, semi-solid medium. Direct immersion of shoot tips in LN has recently resulted in plant recovery rates as high as with the programmed cooling protocol. Further work on cassava cryopreservation includes the logistical aspects for establishing a cassava in vitro base gene bank in LN